Pengaruh Aplikasi Kabita Terhadap Peningkatan Keterampilan Ibu Balita Mengenai Pola Asuh, Pola Makan, Dan Sanitasi - Supardi, Nurjannah; Azis, Marlina; Alza, Nurfaizah; Wahid, Hilmiati (Madu : Jurnal Kesehatan, 2023)
Babies and toddlers are part of a life cycle characterized by rapid physical growth and social development. Stunting experienced by children is a condition of long-term nutritional deficiency as well as the result of repeated infections and environmental factors. Parents should be skilled in caring for children so that stunting can be avoided. Skills improvement alternatives can be accessed by using the KABITA family-based application. The aim of the research is to determine the effect of using the KABITA family-based growth and development application on improving the skills of mothers of toddlers regarding parenting, eating patterns and sanitation. The research method uses a quasi-experimental design with a pre and post with control group design. The sample in this study was 60 people, with 30 people in the control group without using the application and 30 people in the intervention group using the application for one month. The research was conducted in the working area of the Turikale Community Health Center, Maros Regency. The research instruments used were questionnaire sheets, observation sheets, and the KABITA application. Data analysis used the Mann Whitney statistical test. The results showed that there was a significant difference between the knowledge of the intervention group in the pretest and posttest scores (p value = <0.05). There was also a significant difference in the posttest results of the skill levels of the intervention group and the control group (p value = <0.05). The conclusion of this research shows that using the KABITA application can improve the